2022
DOI: 10.1007/s13280-022-01806-z
|View full text |Cite
|
Sign up to set email alerts
|

Has the IPCC’s revised vulnerability concept been well adopted?

Abstract: In the Third and Fourth Assessment Reports (TAR and AR4, respectively) by the Intergovernmental Panel on Climate Change (IPCC), vulnerability is conceived as a function of exposure, sensitivity, and adaptive capacity. However, in its Special Report on Managing the Risks of Extreme Events and Disasters to Advance Climate Change Adaptation (SREX) and Fifth Assessment Report (AR5), the IPCC redefined and separated exposure, and it reconceptualized vulnerability to be a function of sensitivity and capacity to cope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 96 publications
2
7
0
Order By: Relevance
“…By classifying frameworks of vulnerability assessments on marine fisheries to a two‐tier structure, we identified the IPCC 2001/2007 framework as the most commonly applied framework among CVAs cited in the literature to date (55 of 65 studies; Figure 2). This observation resonated with a recent study that assessed the adoption of IPCC's revised vulnerability concept in the broader research area of climate vulnerability, which showed that the IPCC 2001/2007 vulnerability concept continues to predominate and to be used across studies (Estoque et al, 2022). This result was attributed to researchers' preference, possible misinterpretation, and unawareness of the reconceptualization (Estoque et al, 2022).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…By classifying frameworks of vulnerability assessments on marine fisheries to a two‐tier structure, we identified the IPCC 2001/2007 framework as the most commonly applied framework among CVAs cited in the literature to date (55 of 65 studies; Figure 2). This observation resonated with a recent study that assessed the adoption of IPCC's revised vulnerability concept in the broader research area of climate vulnerability, which showed that the IPCC 2001/2007 vulnerability concept continues to predominate and to be used across studies (Estoque et al, 2022). This result was attributed to researchers' preference, possible misinterpretation, and unawareness of the reconceptualization (Estoque et al, 2022).…”
Section: Resultssupporting
confidence: 56%
“…This observation resonated with a recent study that assessed the adoption of IPCC's revised vulnerability concept in the broader research area of climate vulnerability, which showed that the IPCC 2001/2007 vulnerability concept continues to predominate and to be used across studies (Estoque et al, 2022). This result was attributed to researchers' preference, possible misinterpretation, and unawareness of the reconceptualization (Estoque et al, 2022). Another practical reason suggested by our review is that the old paradigm appears to be more established with the development of several high‐impact and operational frameworks, such as the indicator‐based approach from Allison et al (2009), the social–ecological framework developed by Marshall et al (2013), and the trait‐based assessment tool based on Chin et al (2010) and Hare et al (2016), all of which are based on the IPCC 2001/2007 concept.…”
Section: Resultssupporting
confidence: 56%
“…Using these simplified indicators (resistance, recovery, resilience) we also identified patterns of vulnerability, as we explain in Section 3.2.5. Vulnerability has been conceptualized in multiple and sometimes incongruent ways, and it is often a source of discrepancies between schools of thought (e.g., Estoque et al, 2023). For this article we conceived vulnerability as a function of exposure, sensitivity and adaptive capacity (IPCC, 2007), which is one of the most popular definitions (Estoque et al, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Vulnerability has been conceptualized in multiple and sometimes incongruent ways, and it is often a source of discrepancies between schools of thought (e.g., Estoque et al, 2023). For this article we conceived vulnerability as a function of exposure, sensitivity and adaptive capacity (IPCC, 2007), which is one of the most popular definitions (Estoque et al, 2023). We use the measured livestock dynamics to roughly approximate vulnerability patterns with the community.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This approach is strongly rooted in the climate/impacts modeling community, seeks to quantify vulnerability at different levels of warming and how it may change over time (including creating indices of vulnerability), and often focuses on regional scales (Ford et al., 2018; Nightingale, 2016; Preston et al., 2011; Smit & Wandel, 2006). Within the context of the IPCCs revised framing of vulnerability as a component of risk, this is analogous to the concept of exposure (Estoque et al., 2023). While focused largely on projecting biophysical changes, to varying degrees this work also integrates how socio‐economic factors may offset or magnify projected impacts through potential adaptation and behavioral changes (Garschagen et al., 2021; Lanlan et al., 2023; Preston et al., 2011).…”
Section: Introductionmentioning
confidence: 99%